Integrasi KeIslaman Dalam Kurikulum Clinical Skills PSPD Uin Maulana Malik Ibrahim Malang - Riskiyah, Riskiyah; Susanti, Nur Laili (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2023)
Background: A medical education curriculum that integrates Islamic content is necessary for Muslim doctors. Implementing Islamic integration in medical science must be reflected in curriculum development and learning. Objective: This research aims to determine how Islamic integration is implemented in the CSL curriculum in the Medical Education Study Program at UIN Maulana Malik Ibrahim Malang. Method: This research used a qualitative phenomenological with purposive sampling. In-depth interviews were conducted with 16 people, namely ten students and six lecturers, at the UIN Malang Medical Education Study Program. Results: The results of the research found six themes, including Islamic integration was still lacking in the CSL curriculum; Islamic values material that needed to be integrated into the CSL curriculum; Forms of activities that incorporate Islamic values into the CSL curriculum; Needed to include Islamic integration in the assessment OSCE; There needed to be a guidebook in the form of a CSL module that contains the theory and practice of Islamic integration; Prepared lecturers as role models for doctors who apply Islamic values in the CSL curriculum. Conclusion: The integration of Islam in the CSL curriculum still has many shortcomings that need to be improved.